Changes in length-at-first return of a sea trout (Salmo trutta) population in northern France - Josset, Quentin; Beaulaton, Laurent; Romakkaniemi, Atso; Nevoux, Marie (Peer Community Journal)

(untitled)
The resilience of sea trout populations is increasingly concerning, with evidence of major demographic changes in some populations. Based on trapping data and related scale collection, we analysed long-term changes in body length of a sea trout population in the Bresle River, France. From 1984-2022, the length of first-time returning individuals decreased by 1.73 mm.year-1 (SD = 0.08), which resulted in the loss of c. 12.3% of mean body length. This decrease results from a decrease in the age at first return, with a gradual loss of the oldest individuals and an increase in the proportion of the youngest. Timing of the return migration advanced drastically, although shorter sea sojourn had little influence on body length. We found little evidence of a decrease in length-at-age, to the exception of the oldest age class, suggesting that growth conditions at sea might not have deteriorated greatly during the study period.